THE USE OF TEAM GAMES TOURNAMENT MODEL TO IMPROVE SPEAKING SKILLS OF GRADE V ELEMENTARY SCHOOL STUDENTS - Imanah, Sufriah; Much Arsyad Fardani; Siti Masfuah (Indonesian Journal of Educational Development (IJED), 2025)
This research is motivated by monotonous learning by only using peer tutoring model can cause students' limitation in speaking. The purpose of this study was to improve students' speaking skills in the material of unggah-ungguh basa using the Teams Games Tournament model assisted by picture card media. Classroom Action research method consisting of 2 cycles with 2 meetings each. The research subjects in class V SD 7 Kandangmas in 2024/2025 were 13 students with 6 boys and 7 girls. The data analysis techniques used were quantitative and qualitative. Qualitative data were obtained from observations and interviews, while quantitative data through performance tests. The success criteria of this study were determined by the completeness value of students' speaking skills reaching the minimum score, which is ≥75. The results showed an increase in the assessment of students' speaking skills by applying the Teams Games Tournament learning model assisted by picture card media. In cycle I, the average value of students' speaking skills was 71.08 with an unfinished category, improvements were made in cycle II and increased to 86.15 with a completed category. The score in cycle II has reached the success criteria of ≥75, so this research is considered successful and the cycle is stopped.